Tribute to Michel Armand: from Rocking Chair – Li-ion to Solid-State Lithium Batteries. Issue 7 (1st January 2020) - Mauger, Alain; Julien, Christian M.; Goodenough, John B.; Zaghib, Karim
Abstract : Professor Michel Armand is one of the world's leading scientists in the R&D of modern energy storage systems. His scientific works have been devoted to the concepts and technologies of today's batteries, in particular, mastering research on electrodes and electrolytes. With respect to innovative discoveries, Michel had several scientific breakthroughs from the description of the solid-solution electrode and rocking-chair battery to the applications of novel materials utilized in all-solid-state batteries (SSBs); these refer to Li-ion, Na-ion, Li-S, and Li-air cells. At a young age, he formalized the concept of electrochemical intercalation and fabricated the first SSB with sodium-intercalated graphite as the electrode in 1972. Subsequently, he led the use of solid polymer electrolytes and developed lithium-metal-polymer batteries with vanadium oxide as the cathode in 1978. Michel successfully conducted research in new salts topics based on delocalized anions of the sulfonimide family in 1986; his research areas included 1) organic electrode materials, i.e., innovations in redox-active organics, which included poly quinones and aromatic dicarboxylates, and 2) carbon "nano painting" process that has made LiFePO4 @C the safest cathode in 2002. Because Michel has co-authored over 500 publications and many patents, it is impractical to fully review his outstanding contributions in electrochemistry in this work. This work is limited to a few of his contributions pertaining to the evolution of electrochemical energy storage. We further discussed different routes envisioned for further progress in rechargeable batteries.